Comparison of broiler rations sold in Rio Grande do Sul, Brazil. III. Economic profits - Trindade, D. Sturm; Prestes, P. J. de Queiroz; Oliveira, S. Corrêa; Oliveira, W. Miranda de; Müller, Sérgio; Azevedo, L. A. de Paoli; Cavalheiro, A. C. Lopes (Pesquisa Agropecuaria Brasileira, 2014)
Six different commercial broiler rations were compared as to performance and economic aspects. The six rations selected were those sold in the greatest volume. Significant differences in gain of weight and feed conversion were found. However, these data alone were insufficient to classify the rations according to their economic value. It was necessary to consider the total production cost to determine the most profitable ration.